Correcting historical errors in lower eyelid reconstruction - Alexei Almeida Andrade; Renato da Silva Freitas (Revista Brasileira de Cirurgia Plástica)
The history of plastic surgery is very rich, with the description of various types of flaps and other surgical techniques over the centuries. Many authors in the nineteenth and early twentieth centuries proposed the development of surgical flaps for the reconstruction of the periorbital region, which allowed the repair of eyelid deformities at the time and still remain of great clinical applicability to date. Owing to the presence of myriads of techniques and eponyms, often describing identical or very similar techniques, a plastic surgeon often feels confused while reading the description of a technique that was learned under another name during training. Sometimes, even in academic applications and evaluations, these techniques may be presented with unusual nomenclatures, alluding to the diffuser rather than to the creator of the technique, leading to misunderstandings and errors. This review aims to correct some historical errors, assisting new surgeons who wish to work in this area.